Heat-reflective fireproof thermal insulation film material and preparation method thereof

By designing a three-layer structure of thermal reflection fire-proof insulation film, combined with specific raw materials and process processing, the existing fold-resistant polyester reflective film has been solved, and good fire-proof, insulation and reflection performance have been achieved. Improve product quality and market applicability.

CN118418561BActive Publication Date: 2024-12-17JIANGSU VEIK TECH & MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410889711.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2024-12-17
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

The flame retardant and thermal insulation properties of the existing fold-resistant polyester reflective films are insufficient, and further improvements are needed to improve their fire resistance and thermal insulation properties.

Method used

Designed with a three-layer structure of thermal reflection fire-proof insulation film, in which the reflective layer consists of polyethylene terephthalate, reflective masterbatch, polypropylene, antioxidant and PA microbeads, and the base layer is composed of polyterephthalic acid Ethylene glycol esters, reflective masterbatches, polypropylene, antioxidants and insulation masterbatches are composed of a single screw extrusion mechanism and formed an ABA three-layer film structure, combining longitudinal stretching, transverse stretching, thermal setting, cooling, Traction, winding and slitting processes.

Benefits of technology

The heat-reflective fire-proof insulation film has achieved good fire-proof performance, excellent insulation performance and excellent reflectivity, which has improved its quality and market prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of reflective film production, in particular to a heat-reflective fireproof thermal insulation film material and a preparation method thereof; the heat-reflective fireproof thermal insulation film material is a three-layer structure, wherein the middle layer is a base layer, and reflective layers are arranged on both sides of the base layer; the reflective layer is composed of the following raw materials in parts by weight: 20 to 30 parts of polyethylene terephthalate, 3 to 6 parts of reflective masterbatch, 3 to 5 parts of polypropylene, 2 to 4 parts of antioxidant and 4 to 7 parts of PA microbeads; the base layer is composed of the following raw materials in parts by weight: 30 to 40 parts of polyethylene terephthalate, 4 to 8 parts of reflective masterbatch, 2 to 4 parts of polypropylene, 2 to 4 parts of antioxidant and 2 to 4 parts of thermal insulation masterbatch; the heat-reflective fireproof thermal insulation film material prepared by the invention not only has good fireproof performance, but also has excellent thermal insulation performance and excellent reflectivity, thereby effectively ensuring its quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of reflective film production, in particular to a heat reflective fireproof thermal insulation film material and a preparation method thereof. Background Art

[0002] According to the structure, reflective film can be divided into reflective film with reflectivity coating and uncoated reflective film. There are four main methods for preparing reflective film: coating method, multilayer film method, blending method, and microporous method. According to different preparation methods, reflective films with different uses can be obtained.

[0003] A patent document with application number "CN201511021787.0" and titled "A folding-resistant polyester reflective film and a preparation method thereof" discloses a folding-resistant polyester reflective film and a preparation method thereof, characterized in that the reflective film has an ABA three-layer structure; in the ABA three-layer structure of the reflective film, the thickness of an A layer structure accounts for 4-10% of the total thickness, and the thickness of the B layer accounts for 80-92% of the total thickness; the material of the A layer includes polyester resin and inorganic particles, the content of the polyester resin is 80-98%, and the content of the inorganic particles is 2- 20%; the material of the B layer includes polyester resin, inorganic particles, incompatible resin α, incompatible resin β, toughening resin, chain extender, nucleating agent, and dispersant, the content of polyester resin is 30-92%, the content of inorganic particles is 2-30%, the content of incompatible resin α is 2-15%, the content of incompatible resin β is 2-15%, the content of toughening resin is 0.5-5%, the content of chain extender is 0.5-2%, the content of nucleating agent is 0.5-2%, and the content of dispersant is 0.5-1%; the percentages are weight percentages.

[0004] Although the reflective film manufactured by the above patent document has advantages such as high reflectivity, its flame retardant and thermal insulation properties are relatively insufficient and still need to be further improved. Based on this, the present invention provides a heat reflective fireproof thermal insulation film material and a preparation method thereof to solve the above technical problems! Summary of the invention

[0005] The purpose of the present invention is to provide a heat-reflective fireproof thermal insulation film material and a preparation method thereof. The heat-reflective fireproof thermal insulation film material prepared by the present invention not only has good fireproof performance, but also has excellent thermal insulation performance and excellent reflectivity, which effectively guarantees its quality.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a heat-reflective fireproof thermal insulation film material, wherein the heat-reflective fireproof thermal insulation film material has a three-layer structure, wherein the middle layer is a base layer, and reflective layers are arranged on both sides of the base layer;

[0008] The reflective layer is composed of the following raw materials in parts by weight: 20 to 30 parts of polyethylene terephthalate, 3 to 6 parts of reflective masterbatch, 3 to 5 parts of polypropylene, 2 to 4 parts of antioxidant and 4 to 7 parts of PA microbeads;

[0009] The base layer is composed of the following raw materials in parts by weight: 30 to 40 parts of polyethylene terephthalate, 4 to 8 parts of reflective masterbatch, 2 to 4 parts of polypropylene, 2 to 4 parts of antioxidant and 2 to 4 parts of thermal insulation masterbatch.

[0010] Furthermore, the preparation process of the reflective masterbatch is as follows:

[0011] Put an appropriate amount of nano titanium dioxide base material into an appropriate amount of toluene at a dosage ratio of 0.32-0.42 g / mL and ultrasonically disperse for 20-30 minutes, then add concentrated hydrochloric acid (0.12-0.34% by mass of the nano titanium dioxide base material) and 0.2-0.5% 3-aminopropyltriethoxysilane, and react at 100-105°C for 20-22 hours;

[0012] After the reaction is completed, wash with anhydrous ethanol for 2 to 3 times, filter and dry to obtain a dry product. Mix 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with the obtained dry product in a mass ratio of 1:2, place in a sealed container, and introduce CO2 to exclude air. Treat at 50-54°C and 10-12MPa for 7-8h, then wash with deionized water for 2-3 times, and obtain a reflective masterbatch after vacuum drying.

[0013] Furthermore, the preparation process of the nano titanium dioxide base material is as follows:

[0014] Add an appropriate amount of nano-titanium dioxide in an appropriate amount of distilled water at a dosage ratio of 0.08-0.22 g / mL and ultrasonically disperse for 20-30 minutes to obtain a dispersion liquid, then add an appropriate amount of anhydrous sodium carbonate and a composite liquid in a mass ratio of 0.02-0.12:0.24-0.44:1 to the obtained dispersion liquid, and react at 52-55°C for 120-130 minutes;

[0015] After the reaction is completed, the mixture is filtered and washed with anhydrous ethanol and deionized water for 2 to 3 times respectively to obtain modified nano titanium dioxide. The modified nano titanium dioxide is then placed in an appropriate amount of anhydrous ethanol at a dosage ratio of 0.02 to 0.08 g / mL, and centrifuged at 4000 to 4200 r / min for 20 to 30 minutes. The centrifugal product is washed with anhydrous ethanol and deionized water for 2 to 3 times respectively, and then dried at a temperature of 70 to 100° C. to constant weight. The final product is the nano titanium dioxide base material.

[0016] Furthermore, the preparation process of the composite liquid is as follows:

[0017] Add an appropriate amount of octadecyltrimethylammonium chloride into an appropriate amount of distilled water at a mass ratio of 0.06 to 0.14:1, and mix evenly at 40 to 50 r / min to obtain a mixed solution;

[0018] Then, triethanolamine, anhydrous ethanol and the mixed solution are fully mixed in a mass ratio of 0.01-0.03:0.08-0.24:1 to obtain a composite solution.

[0019] Furthermore, the antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.

[0020] Furthermore, the preparation process of the thermal insulation masterbatch is as follows:

[0021] Place an appropriate amount of composite microbeads in an appropriate amount of deionized water at a dosage ratio of 0.02 to 0.12 g / mL and ultrasonically disperse for 20 to 30 minutes to obtain a suspension;

[0022] The pH value of the suspension is adjusted to 2-3 with hydrochloric acid, and then heated to 74-76°C, and then 0.3-0.5% tetrachlorosilane solution of the volume of the suspension is added dropwise, and the heat treatment is carried out for 60-70 minutes. The obtained product is washed with anhydrous ethanol and deionized water for 2-4 times, respectively, and treated in a drying oven at 105-110°C for 120-130 minutes, and then placed in a muffle furnace and calcined at 800-820°C for 60-70 minutes to obtain a heat-insulating masterbatch.

[0023] Furthermore, the composite microbeads are compounded by mixing PS microbeads and PMMA microbeads in a mass ratio of 1:0.5 to 0.8.

[0024] Furthermore, the tetrachlorosilane solution is prepared by compounding tetrachlorosilane and ether in a mass ratio of 0.2 to 0.4:1.

[0025] The second aspect of the present invention further provides a method for preparing the above-mentioned heat-reflective fireproof thermal insulation film material, comprising the following steps:

[0026] Step 1: accurately weigh polyethylene terephthalate, reflective masterbatch, polypropylene, antioxidant and PA microbeads required for preparing the reflective layer, and put them into a single screw extruder at a temperature of 270-280° C. to obtain melt A;

[0027] Step 2: accurately weigh the polyethylene terephthalate, reflective masterbatch, polypropylene, antioxidant and 2 thermal insulation masterbatch required for preparing the base layer, and put them into a single screw extruder at a temperature of 270-280° C. to obtain melt B;

[0028] Step 3: Melt A and melt B are extruded through a laminating device to form an ABA three-layer film structure, which is cooled and solidified to obtain a thick sheet, which is then longitudinally stretched, transversely stretched, heat-set, cooled, pulled, rolled and slit to obtain a finished heat-reflective fireproof thermal insulation film material.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention uses nano titanium dioxide and octadecyl trimethyl ammonium chloride as raw materials to prepare a nano titanium dioxide base material. After the prepared nano titanium dioxide base material is put into an appropriate amount of toluene for ultrasonic dispersion, concentrated hydrochloric acid and 3-aminopropyl triethoxysilane are added thereto for reaction, and then the base material is fully mixed with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, placed in a sealed container, and CO2 is introduced to exclude air, and the base material is aged to obtain a reflective masterbatch. Polyethylene terephthalate, reflective masterbatch, polypropylene, antioxidant and PA microbeads are used as reflective layer raw materials, and polyethylene terephthalate, reflective masterbatch, polypropylene, antioxidant and thermal insulation masterbatch are used as base raw materials, a melt is obtained by a single screw extruder, and then an ABA three-layer film structure is formed by extrusion through a laminating device, and a heat-reflective fireproof thermal insulation film material finished product is obtained through longitudinal stretching, transverse stretching, heat setting, cooling, traction, winding and slitting. The heat-reflective fireproof thermal insulation film material prepared by the present invention not only has good fireproof performance, but also has excellent thermal insulation performance and excellent reflectivity, which effectively guarantees its quality. The heat-reflective fireproof thermal insulation film material and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Embodiment 1: This embodiment provides a heat-reflective fireproof thermal insulation film material, which has a three-layer structure, wherein the middle layer is a base layer, and reflective layers are arranged on both sides of the base layer.

[0033] It should be noted that the thickness of a reflective layer accounts for 4% of the total thickness.

[0034] The reflective layer is composed of the following raw materials in parts by weight: 20 parts of polyethylene terephthalate, 3 parts of reflective masterbatch, 3 parts of polypropylene, 2 parts of antioxidant and 4 parts of PA microbeads;

[0035] The base layer is composed of the following raw materials in parts by weight: 30 parts of polyethylene terephthalate, 4 parts of reflective masterbatch, 2 parts of polypropylene, 2 parts of antioxidant and 2 parts of thermal insulation masterbatch.

[0036] In this embodiment, it should be noted that polyethylene terephthalate was purchased from Dongguan Kaiwan Engineering Plastic Raw Materials Co., Ltd. (Model Z6018), polypropylene was purchased from Shanghai Shunshi Plastic Chemical Co., Ltd. (Model Y16), and PA microbeads were purchased from Dongguan Xingyuan Chemical Co., Ltd. (XY16).

[0037] Further, the preparation process of the reflective masterbatch is as follows:

[0038] An appropriate amount of nano-titanium dioxide base material was added into an appropriate amount of toluene at a dosage ratio of 0.32 g / mL and ultrasonically dispersed for 20 minutes, and then 0.12% of concentrated hydrochloric acid and 0.2% of 3-aminopropyltriethoxysilane were added thereto, and the mixture was reacted at 100°C for 20 hours;

[0039] After the reaction is completed, wash with anhydrous ethanol twice, filter and dry to obtain a dry product. Mix 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with the obtained dry product in a mass ratio of 1:2, place in a sealed container, and introduce CO2 to exclude air. Treat at 50°C and 10MPa for 7h, then wash with deionized water twice, and obtain the reflective masterbatch after vacuum drying.

[0040] In this embodiment, it should be noted that nano titanium dioxide was purchased from Hubei Wei's Chemical Reagent Co., Ltd. (model 13463-67-7).

[0041] Furthermore, the preparation process of the nano titanium dioxide base material is as follows:

[0042] Add an appropriate amount of nano-titanium dioxide in an appropriate amount of distilled water at a dosage ratio of 0.08 g / mL and ultrasonically disperse for 20 minutes to obtain a dispersion, then add an appropriate amount of anhydrous sodium carbonate and the composite liquid in a mass ratio of 0.02:0.24:1 to the obtained dispersion, and react at 52°C for 120 minutes;

[0043] After the reaction is completed, the mixture is filtered and washed twice with anhydrous ethanol and deionized water respectively to obtain modified nano-titanium dioxide. The modified nano-titanium dioxide is then placed in an appropriate amount of anhydrous ethanol at a dosage ratio of 0.02 g / mL and centrifuged at 4000 r / min for 20 minutes. The centrifugal product is washed twice with anhydrous ethanol and deionized water respectively, and then dried at 70°C to constant weight. The final product is the nano-titanium dioxide base material.

[0044] The preparation process of the composite liquid is as follows:

[0045] Add an appropriate amount of octadecyltrimethylammonium chloride into an appropriate amount of distilled water at a mass ratio of 0.06:1, and mix evenly at 40 r / min to obtain a mixed solution;

[0046] Then, triethanolamine, anhydrous ethanol and the mixed solution are fully mixed in a mass ratio of 0.01:0.08:1 to obtain a composite solution.

[0047] In addition, antioxidant 1010 is selected as the antioxidant.

[0048] Among them, the preparation process of thermal insulation masterbatch is as follows:

[0049] An appropriate amount of composite microbeads was placed in an appropriate amount of deionized water at a dosage ratio of 0.02 g / mL and ultrasonically dispersed for 20 min to obtain a suspension;

[0050] The pH of the suspension was adjusted to 2 with hydrochloric acid, and then heated to 74°C, and then a tetrachlorosilane solution of 0.3% by volume of the suspension was added dropwise, and the mixture was kept warm for 60 minutes. The obtained product was washed twice with anhydrous ethanol and deionized water, respectively, and treated in a drying oven at 105°C for 120 minutes. Then, the product was placed in a muffle furnace and calcined at 800°C for 60 minutes to obtain a thermal insulation masterbatch.

[0051] Furthermore, the composite microbeads are compounded by mixing PS microbeads and PMMA microbeads in a mass ratio of 1:0.5.

[0052] In this embodiment, it should be noted that PS microbeads were purchased from Zhongke Leiming (Beijing) Technology Co., Ltd. (model 9003-53-6), and PMMA microbeads were purchased from Dongguan Xinfeng Plastic Trading Co., Ltd. (model BR-101).

[0053] The tetrachlorosilane solution is prepared by mixing tetrachlorosilane and ether in a mass ratio of 0.2:1.

[0054] In addition, this embodiment also provides a method for preparing the above-mentioned heat-reflective fireproof thermal insulation film material, comprising the following steps:

[0055] Step 1: accurately weigh polyethylene terephthalate, reflective masterbatch, polypropylene, antioxidant and PA microbeads required for preparing the reflective layer, and put them into a single screw extruder at a temperature of 270° C. to obtain melt A;

[0056] Step 2: accurately weigh the polyethylene terephthalate, reflective masterbatch, polypropylene, antioxidant and thermal insulation masterbatch required for preparing the base layer, and put them into a single screw extruder at a temperature of 270° C. to obtain melt B;

[0057] Step 3: Melt A and melt B are extruded through a laminating device to form an ABA three-layer film structure, which is cooled and solidified to obtain a thick sheet, which is then longitudinally stretched, transversely stretched, heat-set, cooled, pulled, rolled and slit to obtain a finished heat-reflective fireproof thermal insulation film material.

[0058] Example 2: The preparation method of the heat-reflective fireproof thermal insulation film material provided in this example is basically the same as that in Example 1, except that: the specific raw material composition of the heat-reflective fireproof thermal insulation film material and the specific preparation method of the heat-reflective fireproof thermal insulation film material in this example are different; the specific raw material composition of the heat-reflective fireproof thermal insulation film material and the specific preparation method of the heat-reflective fireproof thermal insulation film material in this example are as follows:

[0059] The invention discloses a heat-reflective fireproof thermal insulation film material, which has a three-layer structure, wherein the middle layer is a base layer, and reflective layers are arranged on both sides of the base layer.

[0060] It should be noted that the thickness of a reflective layer accounts for 4% of the total thickness.

[0061] The reflective layer is composed of the following raw materials in parts by weight: 25 parts of polyethylene terephthalate, 4 parts of reflective masterbatch, 4 parts of polypropylene, 3 parts of antioxidant and 5 parts of PA microbeads;

[0062] The base layer is composed of the following raw materials in parts by weight: 35 parts of polyethylene terephthalate, 6 parts of reflective masterbatch, 3 parts of polypropylene, 3 parts of antioxidant and 3 parts of thermal insulation masterbatch.

[0063] In this embodiment, it should be noted that polyethylene terephthalate was purchased from Dongguan Kaiwan Engineering Plastic Raw Materials Co., Ltd. (Model Z6018), polypropylene was purchased from Shanghai Shunshi Plastic Chemical Co., Ltd. (Model Y16), and PA microbeads were purchased from Dongguan Xingyuan Chemical Co., Ltd. (XY16).

[0064] Further, the preparation process of the reflective masterbatch is as follows:

[0065] An appropriate amount of nano-titanium dioxide base material was added into an appropriate amount of toluene at a dosage ratio of 0.37 g / mL and ultrasonically dispersed for 25 minutes. Then, concentrated hydrochloric acid (0.23% by weight of the nano-titanium dioxide base material) and 0.3% 3-aminopropyltriethoxysilane were added thereto and reacted at 102°C for 21 hours.

[0066] After the reaction is completed, wash with anhydrous ethanol for 3 times, filter and dry to obtain a dry product. Mix 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with the obtained dry product in a mass ratio of 1:2, place in a sealed container, and introduce CO2 to exclude air. Treat at 52°C and 11MPa for 8h, then wash with deionized water for 3 times, and obtain the reflective masterbatch after vacuum drying.

[0067] In this embodiment, it should be noted that nano titanium dioxide was purchased from Hubei Wei's Chemical Reagent Co., Ltd. (model 13463-67-7).

[0068] Furthermore, the preparation process of the nano titanium dioxide base material is as follows:

[0069] Add an appropriate amount of nano-titanium dioxide in an appropriate amount of distilled water at a dosage ratio of 0.1 g / mL and ultrasonically disperse for 25 minutes to obtain a dispersion liquid, then add an appropriate amount of anhydrous sodium carbonate and the composite liquid in a mass ratio of 0.08:0.34:1 to the obtained dispersion liquid, and react at 53°C for 125 minutes;

[0070] After the reaction is completed, the mixture is filtered and washed three times with anhydrous ethanol and deionized water respectively to obtain modified nano-titanium dioxide. The modified nano-titanium dioxide is then placed in an appropriate amount of anhydrous ethanol at a dosage ratio of 0.06 g / mL and centrifuged at 4100 r / min for 25 min. The centrifugal product is washed three times with anhydrous ethanol and deionized water respectively, and then dried at 85°C to constant weight. The final product is the nano-titanium dioxide base material.

[0071] The preparation process of the composite liquid is as follows:

[0072] Add an appropriate amount of octadecyltrimethylammonium chloride into an appropriate amount of distilled water at a mass ratio of 0.09:1, and mix evenly at 45 r / min to obtain a mixed solution;

[0073] Then, triethanolamine, anhydrous ethanol and the mixed solution are fully mixed in a mass ratio of 0.02:0.16:1 to obtain a composite solution.

[0074] In addition, antioxidant 1076 is selected as the antioxidant.

[0075] Among them, the preparation process of thermal insulation masterbatch is as follows:

[0076] An appropriate amount of composite microbeads was placed in an appropriate amount of deionized water at a dosage ratio of 0.07 g / mL and ultrasonically dispersed for 25 min to obtain a suspension;

[0077] The pH of the suspension was adjusted to 3 with hydrochloric acid, and then heated to 75°C, and then a tetrachlorosilane solution of 0.4% by volume of the suspension was added dropwise, and the mixture was kept warm for 65 minutes. The obtained product was washed 3 times with anhydrous ethanol and deionized water, respectively, and treated in a drying oven at 107°C for 125 minutes. Then, the product was placed in a muffle furnace and calcined at 810°C for 65 minutes to obtain a thermal insulation masterbatch.

[0078] Furthermore, the composite microbeads are compounded by mixing PS microbeads and PMMA microbeads in a mass ratio of 1:0.6.

[0079] In this embodiment, it should be noted that PS microbeads were purchased from Zhongke Leiming (Beijing) Technology Co., Ltd. (model 9003-53-6), and PMMA microbeads were purchased from Dongguan Xinfeng Plastic Trading Co., Ltd. (model BR-101).

[0080] The tetrachlorosilane solution is prepared by mixing tetrachlorosilane and ether in a mass ratio of 0.3:1.

[0081] In addition, this embodiment also provides a method for preparing the above-mentioned heat-reflective fireproof thermal insulation film material, comprising the following steps:

[0082] Step 1: accurately weigh polyethylene terephthalate, reflective masterbatch, polypropylene, antioxidant and PA microbeads required for preparing the reflective layer, and put them into a single screw extruder at a temperature of 275° C. to obtain melt A;

[0083] Step 2: accurately weigh the polyethylene terephthalate, reflective masterbatch, polypropylene, antioxidant and thermal insulation masterbatch required for preparing the base layer, and put them into a single screw extruder at a temperature of 275° C. to obtain melt B;

[0084] Step 3: Melt A and melt B are extruded through a laminating device to form an ABA three-layer film structure, which is cooled and solidified to obtain a thick sheet, which is then longitudinally stretched, transversely stretched, heat-set, cooled, pulled, rolled and slit to obtain a finished heat-reflective fireproof thermal insulation film material.

[0085] Example 3: The preparation method of the heat-reflective fireproof thermal insulation film material provided in this example is basically the same as that in Example 1, except that: the specific raw material composition of the heat-reflective fireproof thermal insulation film material and the specific preparation method of the heat-reflective fireproof thermal insulation film material in this example are different; the specific raw material composition of the heat-reflective fireproof thermal insulation film material and the specific preparation method of the heat-reflective fireproof thermal insulation film material in this example are as follows:

[0086] The invention discloses a heat-reflective fireproof thermal insulation film material, which has a three-layer structure, wherein the middle layer is a base layer, and reflective layers are arranged on both sides of the base layer.

[0087] It should be noted that the thickness of a reflective layer accounts for 4% of the total thickness.

[0088] The reflective layer is composed of the following raw materials in parts by weight: 30 parts of polyethylene terephthalate, 6 parts of reflective masterbatch, 5 parts of polypropylene, 4 parts of antioxidant and 7 parts of PA microbeads;

[0089] The base layer is composed of the following raw materials in parts by weight: 40 parts of polyethylene terephthalate, 8 parts of reflective masterbatch, 4 parts of polypropylene, 4 parts of antioxidant and 4 parts of thermal insulation masterbatch.

[0090] In this embodiment, it should be noted that polyethylene terephthalate was purchased from Dongguan Kaiwan Engineering Plastic Raw Materials Co., Ltd. (Model Z6018), polypropylene was purchased from Shanghai Shunshi Plastic Chemical Co., Ltd. (Model Y16), and PA microbeads were purchased from Dongguan Xingyuan Chemical Co., Ltd. (XY16).

[0091] Further, the preparation process of the reflective masterbatch is as follows:

[0092] An appropriate amount of nano-titanium dioxide base material was added into an appropriate amount of toluene at a dosage ratio of 0.42 g / mL and ultrasonically dispersed for 30 minutes. Then, concentrated hydrochloric acid (0.34% by weight of the nano-titanium dioxide base material) and 0.5% of 3-aminopropyltriethoxysilane were added thereto, and the mixture was reacted at 105°C for 22 hours.

[0093] After the reaction is completed, wash with anhydrous ethanol for 3 times, filter and dry to obtain a dry product. Mix 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with the obtained dry product in a mass ratio of 1:2, place in a sealed container, and introduce CO2 to exclude air. Treat at 54°C and 12MPa for 8h, then wash with deionized water for 3 times, and obtain a reflective masterbatch after vacuum drying.

[0094] In this embodiment, it should be noted that nano titanium dioxide was purchased from Hubei Wei's Chemical Reagent Co., Ltd. (model 13463-67-7).

[0095] Furthermore, the preparation process of the nano titanium dioxide base material is as follows:

[0096] Add an appropriate amount of nano-titanium dioxide in an appropriate amount of distilled water at a dosage ratio of 0.22 g / mL and ultrasonically disperse for 30 minutes to obtain a dispersion liquid, then add an appropriate amount of anhydrous sodium carbonate and the composite liquid in a mass ratio of 0.12:0.44:1 to the obtained dispersion liquid, and react at 55°C for 130 minutes;

[0097] After the reaction is completed, the mixture is filtered and washed three times with anhydrous ethanol and deionized water respectively to obtain modified nano-titanium dioxide. The modified nano-titanium dioxide is then placed in an appropriate amount of anhydrous ethanol at a dosage ratio of 0.08 g / mL and centrifuged at 4200 r / min for 30 min. The centrifugal product is washed three times with anhydrous ethanol and deionized water respectively, and then dried at 100°C to constant weight. The final product is the nano-titanium dioxide base material.

[0098] The preparation process of the composite liquid is as follows:

[0099] Add an appropriate amount of octadecyltrimethylammonium chloride into an appropriate amount of distilled water at a mass ratio of 0.14:1, and mix evenly at 50 r / min to obtain a mixed solution;

[0100] Then, triethanolamine, anhydrous ethanol and the mixed solution are fully mixed in a mass ratio of 0.03:0.24:1 to obtain a composite solution.

[0101] In addition, the antioxidant is antioxidant CA.

[0102] Among them, the preparation process of thermal insulation masterbatch is as follows:

[0103] An appropriate amount of composite microbeads was placed in an appropriate amount of deionized water at a dosage ratio of 0.12 g / mL and ultrasonically dispersed for 30 min to obtain a suspension;

[0104] The pH of the suspension was adjusted to 3 with hydrochloric acid, and then heated to 76°C, and then a tetrachlorosilane solution of 0.5% by volume of the suspension was added dropwise, and the product was kept warm for 70 minutes. The product was washed 4 times with anhydrous ethanol and deionized water, respectively, and placed in a drying oven at 110°C for 130 minutes, and then placed in a muffle furnace and calcined at 820°C for 70 minutes to obtain a thermal insulation masterbatch.

[0105] Furthermore, the composite microbeads are compounded by mixing PS microbeads and PMMA microbeads in a mass ratio of 1:0.8.

[0106] In this embodiment, it should be noted that PS microbeads were purchased from Zhongke Leiming (Beijing) Technology Co., Ltd. (model 9003-53-6), and PMMA microbeads were purchased from Dongguan Xinfeng Plastic Trading Co., Ltd. (model BR-101).

[0107] The tetrachlorosilane solution is prepared by mixing tetrachlorosilane and ether in a mass ratio of 0.4:1.

[0108] In addition, this embodiment also provides a method for preparing the above-mentioned heat-reflective fireproof thermal insulation film material, comprising the following steps:

[0109] Step 1: accurately weigh polyethylene terephthalate, reflective masterbatch, polypropylene, antioxidant and PA microbeads required for preparing the reflective layer, and put them into a single screw extruder at a temperature of 280° C. to obtain melt A;

[0110] Step 2: accurately weigh the polyethylene terephthalate, reflective masterbatch, polypropylene, antioxidant and thermal insulation masterbatch required for preparing the base layer, and put them into a single screw extruder at a temperature of 280° C. to obtain melt B;

[0111] Step 3: Melt A and melt B are extruded through a laminating device to form an ABA three-layer film structure, which is cooled and solidified to obtain a thick sheet, which is then longitudinally stretched, transversely stretched, heat-set, cooled, pulled, rolled and slit to obtain a finished heat-reflective fireproof thermal insulation film material.

[0112] Comparative Example 1: The difference from Example 1 is that an equal amount of nano titanium dioxide is used to replace the reflective masterbatch in this example.

[0113] Comparative Example 2: The difference from Example 1 is that in this example, an equal amount of silicon dioxide is used to replace the thermal insulation masterbatch.

[0114] Performance test: The heat-reflective fireproof thermal insulation film samples provided in Examples 1 to 3 and Comparative Examples 1 to 2 are marked as Examples 1 to 3 and Comparative Examples 1 to 2, respectively; and the relevant properties of the heat-reflective fireproof thermal insulation film materials provided in Examples 1 to 3 and Comparative Examples 1 to 2 are tested as follows:

[0115] 1. Reflection performance test: The test method is HG / T4915-2016, wavelength 550nm.

[0116] 2. Combustion performance grade test: The samples are graded according to EN13501-1:2007+A1:2009.

[0117] 3. Measure the FIGRA, THR600s, SMOGRA and TSP600s parameters of each sample according to the EN 13823 test method.

[0118] 4. Thermal insulation performance test: Use a thermal constant analyzer to test the thermal conductivity of the sample as an indicator of thermal insulation capacity.

[0119] The obtained test data are recorded in Table 1, Table 2 and Table 3 below.

[0120]

[0121]

[0122]

[0123] By comparing and analyzing the relevant data in Table 1, Table 2 and Table 3, it can be seen that the heat-reflective fireproof thermal insulation film material prepared by the present invention not only has good fireproof performance, but also has excellent thermal insulation performance and excellent reflectivity, which effectively guarantees its quality. This shows that the heat-reflective fireproof thermal insulation film material and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0124] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0125] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A heat-reflective fireproof thermal insulation film material, characterized in that: The heat-reflective fireproof thermal insulation film material has a three-layer structure, the middle layer is the base layer, and reflective layers are arranged on both sides of the base layer; The reflective layer is composed of the following raw materials in parts by weight: 20 to 30 parts of polyethylene terephthalate, 3 to 6 parts of reflective masterbatch, 3 to 5 parts of polypropylene, 2 to 4 parts of antioxidant and 4 to 7 parts of PA microbeads; The base layer is composed of the following raw materials in parts by weight: 30 to 40 parts of polyethylene terephthalate, 4 to 8 parts of reflective masterbatch, 2 to 4 parts of polypropylene, 2 to 4 parts of antioxidant and 2 to 4 parts of thermal insulation masterbatch; The preparation process of the reflective masterbatch is as follows: Put an appropriate amount of nano titanium dioxide base material into an appropriate amount of toluene at a dosage ratio of 0.32-0.42 g / mL and ultrasonically disperse for 20-30 minutes, then add concentrated hydrochloric acid (0.12-0.34% by mass of the nano titanium dioxide base material) and 0.2-0.5% 3-aminopropyltriethoxysilane, and react at 100-105°C for 20-22 hours; After the reaction is completed, wash with anhydrous ethanol for 2 to 3 times, filter and dry to obtain a dry product, fully mix 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with the obtained dry product in a mass ratio of 1:2, place in a sealed container, introduce CO2 to exclude air, treat at 50 to 54°C and 10 to 12 MPa for 7 to 8 hours, then wash with deionized water for 2 to 3 times, and obtain a reflective masterbatch after vacuum drying; The preparation process of the nano titanium dioxide base material is as follows: Add an appropriate amount of nano-titanium dioxide in an appropriate amount of distilled water at a dosage ratio of 0.08-0.22 g / mL and ultrasonically disperse for 20-30 minutes to obtain a dispersion liquid, then add an appropriate amount of anhydrous sodium carbonate and a composite liquid in a mass ratio of 0.02-0.12:0.24-0.44:1 to the obtained dispersion liquid, and react at 52-55°C for 120-130 minutes; After the reaction is completed, the mixture is filtered and washed with anhydrous ethanol and deionized water for 2 to 3 times to obtain modified nano titanium dioxide. The modified nano titanium dioxide is then placed in an appropriate amount of anhydrous ethanol at a dosage ratio of 0.02 to 0.08 g / mL, and centrifuged at 4000 to 4200 r / min for 20 to 30 minutes. The centrifugal product is washed with anhydrous ethanol and deionized water for 2 to 3 times, and then dried at 70 to 100° C. to a constant weight. The final product is a nano titanium dioxide base material. The preparation process of the composite liquid is as follows: Add an appropriate amount of octadecyltrimethylammonium chloride into an appropriate amount of distilled water at a mass ratio of 0.06 to 0.14:1, and mix evenly at 40 to 50 r / min to obtain a mixed solution; Then, triethanolamine, anhydrous ethanol and the mixed solution are fully mixed in a mass ratio of 0.01-0.03:0.08-0.24:1 to obtain a composite solution; The preparation process of the thermal insulation masterbatch is as follows: Place an appropriate amount of composite microbeads in an appropriate amount of deionized water at a dosage ratio of 0.02 to 0.12 g / mL and ultrasonically disperse for 20 to 30 minutes to obtain a suspension; The pH of the suspension is adjusted to 2-3 with hydrochloric acid, and then heated to 74-76°C, and then 0.3-0.5% of the volume of the suspension is added dropwise with tetrachlorosilane solution, and the product is kept warm for 60-70 minutes. The obtained product is washed with anhydrous ethanol and deionized water for 2-4 times, respectively, and placed in a drying oven at 105-110°C for 120-130 minutes, and then placed in a muffle furnace and calcined at 800-820°C for 60-70 minutes to obtain a heat preservation masterbatch; The composite microbeads are prepared by compounding PS microbeads and PMMA microbeads in a mass ratio of 1:0.5-0.

8.

2. The heat-reflective fireproof thermal insulation film material according to claim 1, characterized in that: The antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.

3. The heat-reflective fireproof thermal insulation film material according to claim 2, characterized in that: The tetrachlorosilane solution is prepared by compounding tetrachlorosilane and ether in a mass ratio of 0.2 to 0.4:

1.

4. A method for preparing a heat-reflective fireproof thermal insulation film material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: accurately weigh polyethylene terephthalate, reflective masterbatch, polypropylene, antioxidant and PA microbeads required for preparing the reflective layer, and put them into a single screw extruder at a temperature of 270-280° C. to obtain melt A; Step 2: accurately weigh the polyethylene terephthalate, reflective masterbatch, polypropylene, antioxidant and 2 thermal insulation masterbatch required for preparing the base layer, and put them into a single screw extruder at a temperature of 270-280° C. to obtain melt B; Step 3: Melt A and melt B are extruded through a laminating device to form an ABA three-layer film structure, which is cooled and solidified to obtain a thick sheet, which is then longitudinally stretched, transversely stretched, heat-set, cooled, pulled, rolled and slit to obtain a finished heat-reflective fireproof thermal insulation film material.